Effects of Reliability and Global Context on Explicit and Implicit Measures of Sensed Hand Position in Cursor-Control Tasks - Rand, Miya K.; Heuer, Herbert (Frontiers in Psychology, 2016)
In a cursor-control task in which the motion of the cursor is rotated randomly relative to the movement of the hand, the sensed directions of hand and cursor are mutually biased. In our previous study, we used implicit and explicit measures of the bias of sensed hand direction toward the direction of the cursor and found different characteristics. The present study serves to explore further differences and commonalities of these measures. In Experiment 1, we examined the effects of different relative reliabilities of visual and proprioceptive information on the explicitly and implicitly assessed bias of sensed hand direction. In two conditions, participants made an aiming movement and returned to the start position immediately or after a delay of 6 s during which the cursor was no longer visible. The unimodal proprioceptive information on final hand position in the delayed condition served to increase its relative reliability. As a result, the bias of sensed hand direction toward the direction of the cursor was reduced for the explicit measure, with a complementary increase of the bias of sensed cursor direction, but unchanged for the implicit measure. In Experiment 2, we examined the influence of global context, specifically of the across-trial sequence of judgments of hand and cursor direction. Both explicitly and implicitly assessed biases of sensed hand direction did not significantly differ between the alternated condition (trial-to-trial alternations of judgments of hand and cursor direction) and the blocked condition (judgments of hand or cursor directions in all trials). They both substantially decreased from the alternated to the randomized condition (random sequence of judgments of hand and cursor direction), without a complementary increase of the bias of sensed cursor direction. We conclude that our explicit and implicit measures are equally sensitive to variations of coupling strength as induced by the variation of global context in Experiment 2, but are differently sensitive to variations of the relative reliabilities as induced by our additional unimodal proprioceptive information in Experiment 1.